Exploring factors that influence Muslim intention to purchase online - Abdulgani, Montadzah Ambag; Suhaimi, Mohd Adam (IEEE, 2014)
This paper focuses on the factors that influence Muslim intention to purchase online. There are mounting concerns among Muslims regarding online transaction from technological and Shariah perspectives which require researchers to examine. Discussion on the intention to purchase in e-commerce environment can be largely found in the literature; yet, it scarcely looks from the Islamic perspective. Library research is employed to search for information on essential factors underpinning intention to purchase online in e-commerce setting. Review of existing literature sheds light on some conditions related to aspect that influence intention to purchace online such as: Shariah compliant, trust, integrity, competence, benevolence, web quality, third party assurance, trustors propensity, religious commitment, trustworthiness and perceived risk. Investigating these factors will rationalize the concern of Muslim buyers online.